2020
DOI: 10.3390/ijms21186480
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK in Glucose Metabolism of Skeletal Muscle: Beneficial or Harmful?

Abstract: Skeletal muscles respond to environmental and physiological changes by varying their size, fiber type, and metabolic properties. P38 mitogen-activated protein kinase (MAPK) is one of several signaling pathways that drive the metabolic adaptation of skeletal muscle to exercise. p38 MAPK also participates in the development of pathological traits resulting from excessive caloric intake and obesity that cause metabolic syndrome and type 2 diabetes (T2D). Whereas p38 MAPK increases insulin-independent glucose upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 119 publications
(149 reference statements)
0
48
0
Order By: Relevance
“…Mitogen-activated protein kinase (MAPK), mainly consisting of three distinctive cascades, the JNK, p38 and ERK pathways, is a well-known and crucial signaling pathway in multiple diseases (58)(59)(60)(61). In the past decades, the role of MAPK cascade in the TGF-β1-relevant IPF has been gradually elucidated.…”
Section: Mapk-relevant Signaling Pathwaymentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK), mainly consisting of three distinctive cascades, the JNK, p38 and ERK pathways, is a well-known and crucial signaling pathway in multiple diseases (58)(59)(60)(61). In the past decades, the role of MAPK cascade in the TGF-β1-relevant IPF has been gradually elucidated.…”
Section: Mapk-relevant Signaling Pathwaymentioning
confidence: 99%
“…Among them we found MAPK1, which is an activated regulator found in FHL2−/− heart, also a known as an interactor of FHL2. It was previously shown that FHL2 represses MAPK1 activity in cardiomyocytes and this was related to the cardiac hypertrophy response, but MAPK1 is also involved in glucose diffusion and development of insulin resistance in obesity [46,47]. Energy expenditure can be increased by the process of adaptive thermogenesis of BAT, but we found no structural differences, with a trend towards higher expression of the key thermogenic protein UCP1 in FHL2−/− mice and a significant preference for the uptake from the circulation of fatty acids over glucose.…”
Section: Discussionmentioning
confidence: 99%
“…After this activation cascade occurred, increased levels of GLUT4 were produced in the cytosol and then moved to the cell membrane for glucose uptake ( Figure 7 ). Simultaneously, S. pastorianus extract elicited the activation of p38 MAPK, which plays an important role in GLUT4 activation ( Figure 7 ) [ 27 ]. Notably, the expression of PKC was raised in 3T3-L1 cells treated with S. pastorianus extract ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%